High-performance environment-friendly UV adhesive for battery and preparation method thereof

By developing environmentally friendly UV glue with low viscosity, high thixotropy and fast curing, the problems of large space occupation, low production efficiency and low energy density in the edge sealing technology of soft-pack battery are solved, and efficient and environmentally friendly edge sealing effect is achieved, enhancing the performance and safety of the battery.

CN119662201APending Publication Date: 2025-03-21STEADYCHEM (SHANGHAI) CO LTD

Patent Information

Application Number
CN202411916326.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing soft-pack battery edge sealing technology has problems such as large space occupation, low production efficiency, low energy density and complex edge sealing structure, which is difficult to meet the needs of high energy density and miniaturization.

Method used

Develop a low viscosity, high thixotropy, fast curing environmentally friendly UV glue. By optimizing the composition of acrylate prepolymer, the design of composite flexible and hard polyols is adopted to form a crosslinked structure to improve heat resistance and durability.

Benefits of technology

It has achieved simplification of production processes, saving edge sealing space, improving battery energy density, enhancing battery performance and safety, avoiding the problems of increasing size and low production efficiency of traditional edge sealing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206904120000031
    Figure BDA0005206904120000031
  • Figure BDA0005206904120000051
    Figure BDA0005206904120000051
  • Figure BDA0005206904120000161
    Figure BDA0005206904120000161
Patent Text Reader

Abstract

The invention discloses a high-performance environment-friendly UV (ultraviolet) adhesive for batteries and a preparation method thereof, and the UV adhesive is prepared from the following raw materials in parts by weight: 20-50 parts of acrylate prepolymer, 30-70 parts of first acrylate monomer, 1-10 parts of photoinitiator, 5-15 parts of thixotropic agent and 0.5-5 parts of other auxiliaries, the acrylate prepolymer is prepared from the following raw materials: compound polyol, isocyanate and a second acrylate monomer; the compound polyol comprises a flexible polyol and a hard polyol which are compounded according to a molar ratio of 1: (1-5). According to the high-performance environment-friendly UV adhesive for the battery, the viscosity is smaller than 5000 cps, Tg is larger than or equal to 70 DEG C, the elongation at break is larger than or equal to 550%, the shear strength is larger than or equal to 5 MPa, and the resistivity is larger than or equal to 109 omega.m. The UV adhesive disclosed by the invention has the characteristics of low viscosity, high thixotropy, convenience in sizing, short curing time, good flexibility of cured adhesive, high bonding strength and excellent heat resistance and insulating property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmentally friendly adhesives, and in particular relates to a high-performance environmentally friendly UV adhesive for batteries and a preparation method thereof. Background Art

[0002] At present, the edge sealing structure of soft-pack batteries mainly includes two structures: single-folding structure and double-folding structure. The single-folding structure is to stick insulating tape on the edge of the battery packaging edge, and then use mechanical methods to fold the packaging edge and stick it to the side of the battery body; the double-folding structure is to fold the edge of the packaging edge that exposes the metal layer onto the packaging edge body, and then fold the packaging edge body and stick it to the battery body. Through two folds, the edge of the exposed metal layer is clamped between the packaging edge body and the battery body.

[0003] For example, patent CN118431580A discloses a method for preparing a large-diameter cylindrical single-sealed edge soft-pack lithium ion battery, which includes: a cylindrical lithium battery, a single-side sealed edge and a pole ear, step 1: when preparing and packaging the cylindrical lithium battery, the aluminum-plastic shell is stamped into a shell, and the wound battery cell is placed inside the shell for single-side sealed soft-pack packaging; step 2: top and bottom packaging and baking are performed, and the pole ear is exposed; step 3: liquid is injected from the opening on the side where the air bag is left, and then vacuum side sealing is performed; step 4: the battery is pre-formed; step 5: cutting from the air bag sealing edge, using a vacuum sealer to remove the internal gas of the battery and then sealing the side to form a single-side sealed edge, which can effectively control the size of the finished battery. The edge sealing structure of soft-pack batteries mainly adopts the rubber-coated single-folding structure and the double-folding structure. Although these two traditional edge sealing methods can solve the problem of exposed aluminum in conventional batteries, they both have obvious disadvantages: the rubber-coated single-folding structure requires attaching multiple layers of insulating tape to the edge of the package and mechanically folding it, which takes up a large space and reduces the energy density of the battery. At the same time, multiple pasting processes also reduce production efficiency; the double-folding structure increases the thickness of the edge by folding twice, which easily causes the overall size of the battery to exceed the specification, which is not conducive to the development of thin and light electronic equipment. With the increasing requirements for high energy density and miniaturization of soft-pack batteries, the limitations of traditional edge sealing technology make it difficult to meet the needs of modern production.

[0004] Therefore, the industry has begun to explore the solution of replacing traditional technology with UV edge banding adhesive. UV edge banding adhesive can save the folding and tape sticking process, greatly save edge banding space, and improve production efficiency and environmental protection at the same time, becoming an important direction to solve the current edge banding technology problems.

[0005] For example, the invention CN113113703A discloses a cylindrical soft-pack battery edge sealing method and a cylindrical soft-pack battery. The invention makes the edge closely fit on the side wall of the battery body by sticking a fixed yellow glue on the edge, and also by coating a protective glue (UV glue) on the side wall of the soft-pack battery, so as to support, reinforce and protect the edge and the fixed yellow glue. At the same time, it can also protect the fixed yellow glue and the folded edge, so as to improve the service life of the soft-pack battery. Although the invention effectively improves the service life of the battery by using a combination of fixed yellow glue and protective glue to reinforce and protect the edge sealing structure of the soft-pack battery, it still has certain limitations. First of all, although the use of fixed yellow glue to stick the edge to the side wall of the battery body can provide better support and fixation, the overall design of the edge sealing structure still requires additional tape and protective glue coating, which may make the edge sealing process relatively complicated, and still occupy a certain space, affecting the energy density of the battery. In addition, although the use of protective glue (UV glue) can enhance the stability of fixing the yellow glue and the edge wrapping, this step still increases the complexity of the process and the production cycle, and may reduce production efficiency.

[0006] Therefore, how to provide a soft-pack battery edge sealing adhesive with low viscosity, high thixotropy, fast curing and environmental protection to simplify the production process, save edge sealing space, increase battery energy density, and enhance battery performance and safety has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0007] In view of the defects existing in the above-mentioned prior art, the purpose of the present invention is to provide a high-performance environmentally friendly UV glue for batteries and a preparation method thereof. The high-performance environmentally friendly UV glue for batteries is particularly suitable for battery soft packs, has low viscosity, high thixotropy, is easy to apply and has a short curing time. The cured colloid has good flexibility, high bonding strength, heat resistance and excellent insulation properties. It can replace traditional single folding and double folding technologies, solve the problem of exposed aluminum in the battery, and can save battery space with a light and thin size, thereby improving the battery energy density.

[0008] In a first aspect, the present invention provides a high-performance environmentally friendly UV adhesive for batteries, which comprises the following raw materials in parts by weight:

[0009]

[0010] The raw materials of the acrylic ester prepolymer include compounded polyol, isocyanate and a second acrylic ester monomer; the compounded polyol includes a flexible polyol and a hard polyol compounded in a molar ratio of 1:(1-5).

[0011] Preferably, the battery high-performance environmentally friendly UV adhesive has a viscosity of less than 5000cps, a thixotropy of greater than 3.5, preferably greater than 3.8, more preferably greater than 4, a curing depth of greater than 0.5mm, preferably greater than 0.6mm; and a Tg of ≥70°C, an elongation at break of ≥550%, a shear strength of ≥5MPa, and a resistivity of ≥10 9 Ω·m.

[0012] The UV adhesive of the present invention does not need to add any solvent, and the ingredients used are relatively environmentally friendly, do not contain heavy metals, toluene, formaldehyde, etc., and meet relevant domestic and international standards.

[0013] The acrylate prepolymer, an important raw material of the high-performance environmentally friendly UV glue of the present invention, has a compound polyol in the raw material containing a flexible polyol and a hard polyol, which can enhance the bonding strength of the UV glue while improving its flexibility and adaptability, so that the colloid maintains stable performance under changes such as high temperature, low temperature and thermal expansion and contraction of the battery. In addition, the participation of isocyanate and the second acrylate monomer helps to form a cross-linked structure, thereby improving the heat resistance and durability of the UV glue. The high-performance environmentally friendly UV glue has a viscosity of less than 5000cps and a high Tg (≥70°C), and can form a uniform and stable edge sealing layer in a shorter curing time, ensuring the long-term stability of the battery under different environmental conditions. At the same time, its high elongation at break (≥550%), high shear strength (≥5MPa) and excellent resistivity (≥10 9 Ω·m) ensures the good mechanical properties, excellent electrical insulation and thermal stability of the colloid, meets the needs of soft-pack batteries for high energy density and miniaturization, and effectively avoids the problems of size increase and low production efficiency in traditional edge sealing technology.

[0014] Preferably, the flexible polyol has a molecular weight of 1000-5000 Mn and includes at least one of polyether polyol and polyolefin polyol;

[0015] The hard polyol has a molecular weight of 500-2500 Mn and comprises polyester polyol.

[0016] Flexible polyols have longer molecular chains and lower rigidity. Their higher molecular weight enables UV adhesives to have better flexibility and ductility, thereby effectively coping with the expansion and thermal deformation that may occur during the use of the battery, and improving the stability and adaptability of UV adhesives in high and low temperature environments. In addition, flexible polyols help reduce stress concentration in the UV adhesive during the curing process, improve the crack resistance of the overall adhesive layer, and enhance the durability of the battery during use.

[0017] The smaller molecular chain and stronger rigidity of hard polyols make UV glue have higher shear strength and hardness, which effectively improves the adhesion and structural stability of the colloid. Hard polyols enhance the mechanical strength and heat resistance of UV glue, ensuring that the battery can maintain a stable edge sealing effect under high temperature and high load conditions, and can effectively fix the internal components of the battery to avoid battery short circuit or damage caused by UV glue failure. Through reasonable molecular weight selection and content ratio design, the combination of flexible polyols and hard polyols can balance the flexibility and strength of UV glue, thereby achieving efficient edge sealing while improving the overall performance and reliability of soft-pack batteries.

[0018] Preferably, the first acrylate monomer includes at least one of a monofunctional acrylate monomer and a high-functional acrylate monomer, and does not contain a methacrylate monomer.

[0019] Monofunctional acrylate monomers have a single reactive functional group and can effectively react with other monomers to enhance the stability and mechanical properties of the colloid. High-functionality acrylate monomers have multiple reactive functional groups, which help to form a network structure with a higher cross-linking density, thereby improving the bonding strength, heat resistance and anti-aging properties of the UV glue. The use of methacrylate monomers is excluded in order to avoid the low stability and environmental risks that they may bring, while ensuring that the UV glue has better bonding effect and long-term durability. In addition, it is preferred that the first acrylate monomer is a compound of a monofunctional acrylate monomer and a high-functionality acrylate monomer, for example, in a mass ratio of (50-90): (0.1-5), so as to better take into account the advantages of both.

[0020] Preferably, the acrylic ester prepolymer comprises the following raw materials in parts by weight:

[0021]

[0022] The isocyanate includes diisocyanate, and the molar ratio of isocyanate to the flexible polyol is (1-4): 1;

[0023] The molar ratio of isocyanate-terminated acrylate monomer to rigid polyol is (1-5):(1-3);

[0024] The second acrylate monomer includes an acrylate monomer that is unreactive with respect to the isocyanate.

[0025] The second acrylate monomer is an acrylate monomer that is non-reactive to isocyanate, similar to a stable diluent in an acrylate prepolymer system, and can adjust the activity of the reaction system to prevent unnecessary side reactions. The second acrylate monomer does not react with isocyanate, thereby ensuring that only components that need to react react during the synthesis of the acrylate prepolymer. This feature not only ensures the controllability of the synthesis process, but also avoids performance degradation due to side reactions, further improving the stability and reliability of the UV glue. At the same time, the low-viscosity second acrylate monomer can adjust the viscosity of the system, making the acrylate prepolymer in liquid form, improving the processability of the UV glue, and making the glue have better thixotropy and fluidity during sizing, which is easy to operate and apply, improves production efficiency and ensures product consistency.

[0026] Preferably, the isocyanate-terminated acrylate monomer comprises at least one of isocyanate ethyl acrylate and isocyanate ethyl methacrylate; and / or

[0027] The isocyanate-terminated acrylate monomer is prepared by prepolymerization of isocyanate and hydroxyl-containing acrylate monomer, wherein the mass ratio of isocyanate to hydroxyl-containing acrylate monomer is (15-60): (8-35).

[0028] The isocyanate-terminated acrylate monomer may be a common type, but a blocked isocyanate-terminated acrylate monomer is more preferred. This type of monomer participates in the reaction only at high temperatures, has low activity at room temperature, is not easy to react with moisture, etc., and is easier to store.

[0029] Preferably, the UV adhesive satisfies at least one of the following:

[0030] 1) The flexible polyol includes one or more of polyethylene glycol polyol, polypropylene glycol polyol, polytetramethylene glycol polyol, tetramethylene glycol-propylene oxide copolymer glycol, polyethylene polyol, polypropylene polyol, polybutadiene polyol, and polyisoprene polyol;

[0031] 2) The hard polyol includes one or more of aliphatic polyester polyol (such as poly(1,2-ethylene adipate polyol), poly(1,4-butylene adipate polyol), poly(1,6-hexanediol adipate polyol), aromatic polyester polyol, polycaprolactone polyol, and polycarbonate polyol;

[0032] 3) The isocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.

[0033] The flexible polyol, rigid polyol and isocyanate of the present invention have multiple types and combinations thereof to choose from. Through a large number of experimental conclusions, better effects can be obtained only when the above-mentioned type requirements and usage ratios are met.

[0034] Preferably, the UV adhesive satisfies at least one of the following:

[0035] 1) The photoinitiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzophenone, 2,4-dihydroxybenzophenone, Michler's ketone, (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, bicyclic monoterpenoid compounds, and 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone;

[0036] 2) The thixotropic agent includes at least one of nano fumed silica, nano calcium carbonate, nano zinc oxide, nano zirconium oxide, nano aluminum oxide, precipitated silica, nano talc, organic bentonite, and polyamide wax;

[0037] 3) The other auxiliary agents include one or more of coupling agents, matting agents, defoaming agents, antioxidants, and colorants.

[0038] The function of the photoinitiator is to start the curing reaction of UV glue, thereby increasing its curing speed and efficiency. The use of photoinitiators can quickly initiate polymerization reactions under ultraviolet light, shorten curing time, and improve production efficiency. It is particularly suitable for the needs of rapid manufacturing and large-scale production. Photoinitiators can ensure that UV glue can cure quickly even in low temperature environments, thereby effectively improving work efficiency and reducing energy consumption.

[0039] The function of the thixotropic agent is to adjust the rheological properties of the UV glue so that it has good thixotropy, that is, it can maintain a suitable viscosity when applying the glue, can flow and evenly cover the surface after applying pressure, and can restore its original viscosity when it is stationary. The thixotropic agent includes nano-fumed silica, nano-calcium carbonate, nano-zinc oxide, nano-zirconium oxide, nano-alumina, precipitated silica, nano-talc, organic bentonite, polyamide wax, etc. These materials can significantly improve the fluidity and uniformity of the UV glue, reduce dripping, improve the accuracy of glue application, ensure uniform coating of the UV glue, and avoid defects in the production process.

[0040] Other additives in UV glue, such as coupling agents, matting agents, defoaming agents, antioxidants, colorants, etc., can further optimize the edge sealing performance. Coupling agents can improve the adhesion between UV glue and the substrate, matting agents can reduce the surface gloss, defoaming agents can prevent the colloid from generating bubbles during the curing process, affecting the uniformity of the glue layer, and antioxidants can extend the service life of UV glue and prevent it from being affected by oxidation during storage and use. Colorants can be used to adjust the appearance of UV glue to make it more visually attractive in the application or more in line with the appearance requirements of the battery.

[0041] In a second aspect, the present invention further provides a method for preparing the high-performance environmentally friendly UV glue for the battery, comprising the following steps:

[0042] Step 1, preparing an acrylate prepolymer;

[0043] Step 2, stirring and mixing the acrylate prepolymer, part of the first acrylate monomer, the photoinitiator, and part of other additives at 40-50° C. to obtain a mixture;

[0044] Step 3, filtering the mixture, adding a thixotropic agent, and stirring at a temperature below 40° C. to obtain a semi-finished product;

[0045] Step 4: Grind the semi-finished product and mix it with the remaining first acrylate monomer and other additives, stir it at a temperature below 40° C., and perform vacuum degassing to obtain the UV adhesive.

[0046] Preferably, in step three, after the mixture is filtered through a 200-400 mesh double-layer gravity filter, the thixotropic agent is added in batches to facilitate better dispersion of the thixotropic agent, for example, the thixotropic agent is divided into three equal parts and added successively in three times.

[0047] Preferably, the step 4 specifically comprises: grinding the semi-finished product by three rollers, grinding at a speed of 100-300 rpm with an inlet of 20-75 μm and an outlet of 10-30 μm;

[0048] Then add the ground material, the remaining first acrylate monomer and the remaining other additives into the reactor, stir at 30-50rpm, disperse at 800-1200rpm, stir for 40-80 minutes, turn on the vacuum -0.07±0.01Mpa, and perform vacuum degassing and discharge with the parameters of stirring 10-20rpm and dispersing 0-200rpm to obtain the UV glue.

[0049] Preferably, the step 1 includes the following steps:

[0050] S1. Preparation of premixes A to E:

[0051] Mixing a portion of the second acrylate monomer and 30-60% of a polymerization inhibitor to obtain a premix A;

[0052] Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix B;

[0053] Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix C;

[0054] Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix D;

[0055] Mixing a portion of the second acrylate monomer, 20-30% of the catalyst and 40-70% of the inhibitor to obtain a premix E;

[0056] S2, mixing the premix A and the flexible polyol under vacuum at 60-70° C. to obtain an intermediate A;

[0057] S3, cooling to 50-60°C, adding isocyanate to intermediate A, stirring under vacuum, then adding premix B, mixing under vacuum at below 75°C, to obtain intermediate B;

[0058] S4, adding premix C and hard polyol to intermediate B, mixing under vacuum at below 75° C. to obtain intermediate C;

[0059] S5, adding premix D to intermediate C, mixing under vacuum at 65-75° C. to obtain intermediate D;

[0060] S6. Add the premix E and the isocyanate-terminated acrylate monomer to the intermediate D, stir and heat to 85-95° C. under vacuum to obtain the acrylate prepolymer.

[0061] The present invention, without using a solvent, cleverly utilizes a second acrylate monomer with low activity that does not react with isocyanate to obtain multiple important premixes, fully disperses the materials, and is conducive to subsequent sequential addition as the reaction proceeds, controls the reaction rhythm and prepolymer molecular weight, and thus obtains an acrylate prepolymer that meets the subsequent UV glue polymerization requirements.

[0062] Preferably, the weight ratio of the second acrylate monomer in the premix A, premix B, premix C, premix D, and premix E is 1:(1-3):(1-3):(1-4):(1-6). According to the characteristics and dosage of the materials to be premixed, a suitable ratio of the second acrylate monomer is allocated to save dosage and reduce costs while ensuring that all materials are fully premixed.

[0063] The present invention has at least the following beneficial effects:

[0064] (1) The present invention optimizes the composition of the acrylate prepolymer, especially adopts a design of compounding flexible and hard polyols, so that the UV glue has better flexibility while ensuring high bonding strength. The flexible polyol has a longer molecular chain and lower rigidity, which can improve the ductility of the UV glue and ensure that it can cope with the challenges of thermal expansion and thermal deformation during the use of the battery. The hard polyol enhances the mechanical strength of the UV glue and improves the overall stability. Through the ratio and optimization of the above materials, the UV glue of the present invention can still maintain excellent performance in the environmental changes of high temperature, low temperature and thermal expansion and contraction of the battery, avoiding the problem of cracking or falling off caused by insufficient rigidity or poor ductility of traditional edge sealing glue, thereby greatly improving the reliability and service life of the soft-pack battery.

[0065] (2) The present invention forms a cross-linked structure in the UV glue by introducing the cross-linking reaction of isocyanate and acrylate monomers, thereby significantly improving the heat resistance and durability of the UV glue. The addition of isocyanate promotes stronger intermolecular bonding, so that the UV glue can still maintain excellent performance under high temperature or extreme load conditions. Traditional edge sealing adhesives often soften or lose adhesion at high temperatures, resulting in unstable edge sealing and even the risk of loosening or short circuiting of internal battery components. The present invention ensures that the edge sealing layer of the battery is always stable during long-term use by introducing the cross-linking reaction of isocyanate and acrylate monomers, avoiding battery failure problems caused by failure of edge sealing adhesive in traditional technologies, and enhancing the safety and reliability of soft-pack batteries in complex environments.

[0066] (3) The present invention preferably uses UV photoinitiator as one of the initiators of UV glue, which can quickly start the polymerization reaction under ultraviolet irradiation and significantly shorten the curing time. Traditional edge sealing glue often relies on a thermal curing process, which is time-consuming and requires a high temperature environment, limiting the efficiency and energy consumption of the production line. By introducing UV photoinitiator, the present invention can achieve low-temperature rapid curing, which is particularly suitable for the needs of rapid manufacturing and large-scale production. The UV curing process not only greatly improves production efficiency, but also reduces energy consumption, meeting the requirements of modern production lines for fast, efficient and energy-saving. In addition, the use of UV photoinitiator makes the UV glue more controllable during the curing process, ensures the uniformity and stability of the glue layer, avoids the problem of UV glue performance degradation due to incomplete or uneven curing, and further improves the reliability and consistency of the product. DETAILED DESCRIPTION

[0067] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in further detail below.

[0068] A high-performance environmentally friendly UV adhesive for batteries, in particular a UV adhesive for soft-pack batteries, comprises the following raw materials in parts by weight:

[0069] (1) Acrylate prepolymer, 20-50 parts by weight, the raw materials of the acrylate prepolymer specifically include:

[0070] (1.1) flexible polyol, 50-300 parts, molecular weight 1000-5000Mn, including at least one of polyether polyol and polyolefin polyol, preferably including one or more of polyethylene glycol polyol, polypropylene glycol polyol, polytetramethylene glycol polyol, tetramethylene glycol-propylene oxide copolymer glycol, polyethylene polyol, polypropylene polyol, polybutadiene polyol, polyisoprene polyol;

[0071] (1.2) hard polyol, 50-300 parts, molecular weight 500-2500Mn, mainly polyester polyol, preferably including one or more of aliphatic polyester polyol (poly(1,2-ethylene adipate polyol, poly(1,4-butylene adipate polyol, poly(1,6-hexane adipate polyol), aromatic polyester polyol, polycaprolactone polyol, polycarbonate polyol);

[0072] The molar ratio of the flexible polyol to the rigid polyol is 1:(1-5).

[0073] (1.3) isocyanate, 15-60 parts, including one or more of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate; the molar ratio of isocyanate to flexible polyol is (1-4):1;

[0074] (1.4) 50-200 parts of a second acrylate monomer, comprising an acrylate monomer that is non-reactive with respect to the isocyanate;

[0075] (1.5) 15.8-60 parts of an isocyanate-terminated acrylate monomer, including at least one of isocyanate ethyl acrylate and isocyanate ethyl methacrylate, preferably including at least one of blocked isocyanate ethyl acrylate and blocked isocyanate ethyl methacrylate; and / or

[0076] The isocyanate-terminated acrylate monomer is prepared by prepolymerization of isocyanate and hydroxyl-containing acrylate monomer, wherein the mass ratio of the isocyanate and hydroxyl-containing acrylate monomer involved in the prepolymerization is (15-60): (8-35);

[0077] The molar ratio of isocyanate-terminated acrylate monomer to rigid polyol is (1-5):(1-3);

[0078] (1.6) a polymerization inhibitor, 0.01-0.1 parts, including at least one of hydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, 2,6-di-tert-butyl-p-cresol, phenothiazine, p-benzoquinone, and methylhydroquinone;

[0079] (1.7) Catalyst, 0.02-0.1 parts, including at least one of organotin, organobismuth, organic amine and inorganic acid catalysts; wherein the organotin catalyst is at least one selected from dibutyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, dibutyltin diacetate and dibutyltin dichloride;

[0080] (2) 30-70 parts of a first acrylate monomer, wherein the first acrylate monomer comprises at least one of a monofunctional acrylate monomer and a high-functional acrylate monomer, and does not contain a methacrylate monomer;

[0081] (3) a photoinitiator, 1 to 10 parts, including at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzophenone, 2,4-dihydroxybenzophenone, Michler's ketone, (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, bicyclic monoterpenoid compounds, and 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone;

[0082] (4) a thixotropic agent, 5-15 parts, including at least one of nano-fumed silica, nano-calcium carbonate, nano-zinc oxide, nano-zirconium oxide, nano-alumina, precipitated silica, nano-talc, organic bentonite, and polyamide wax;

[0083] (5) Other additives, 0.5-5 parts, including one or more of coupling agents, matting agents, defoaming agents, antioxidants, and colorants. The above-mentioned other additives are commonly used processing aids in the field and can be selected or combined according to the actual product use and other needs.

[0084] The high-performance environmentally friendly UV adhesive for batteries has a viscosity of less than 5000cps, a Tg of ≥70°C, an elongation at break of ≥550%, a shear strength of ≥5MPa, and a resistivity of ≥10 9 Ω·m.

[0085] The preparation method of the high-performance environmentally friendly UV adhesive for the battery comprises the following steps:

[0086] Step 1: preparing an acrylate prepolymer, specifically comprising:

[0087] S1. Preparation of premixes A to E:

[0088] Mixing a portion of the second acrylate monomer and 30-60% of a polymerization inhibitor to obtain a premix A;

[0089] Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix B;

[0090] Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix C;

[0091] Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix D;

[0092] Mixing a portion of the second acrylate monomer, 20-30% of the catalyst and 40-70% of the inhibitor to obtain a premix E;

[0093] S2, mixing the premix A and the flexible polyol under vacuum at 60-70° C. to obtain an intermediate A;

[0094] S3, cooling to 50-60°C, adding isocyanate to intermediate A, stirring under vacuum, then adding premix B, mixing under vacuum at below 75°C, to obtain intermediate B;

[0095] S4, adding premix C and hard polyol to intermediate B, mixing under vacuum at below 75° C. to obtain intermediate C;

[0096] S5, adding premix D to intermediate C, mixing under vacuum at 65-75° C. to obtain intermediate D;

[0097] S6. Add the premix E and the isocyanate-terminated acrylate monomer to the intermediate D, stir and heat to 85-95° C. under vacuum to obtain the acrylate prepolymer.

[0098] The weight ratio of the second acrylic acid ester monomer in the premix A, premix B, premix C, premix D, and premix E is 1:(1-3):(1-3):(1-4):(1-6);

[0099] Step 2, stirring and mixing the acrylate prepolymer, part of the first acrylate monomer, the photoinitiator, and part of other additives at 40-50° C. to obtain a mixture;

[0100] Step 3, filtering the mixture, adding a thixotropic agent, and stirring at a temperature below 40° C. to obtain a semi-finished product;

[0101] Step 4: Grind the semi-finished product and mix it with the remaining first acrylate monomer and other additives, stir it at a temperature below 40° C., and perform vacuum degassing to obtain the UV adhesive.

[0102] With respect to the acrylate prepolymer used in preparing the UV glue of the present invention, the present invention provides the following preparation examples 1-5:

[0103] Preparation Example 1

[0104] The method for preparing the acrylate prepolymer 1 specifically comprises:

[0105] S1. Preparation of premixes A to E:

[0106] Mixing 10 parts of the second acrylate monomer and 0.01 parts of a polymerization inhibitor to obtain a premix A;

[0107] Mixing 20 parts of a second acrylate monomer and 0.01 parts of a catalyst to obtain a premix B;

[0108] Mixing 20 parts of a second acrylate monomer and 0.01 parts of a catalyst to obtain a premix C;

[0109] Mixing 30 parts of a second acrylate monomer and 0.01 parts of a catalyst to obtain a premix D;

[0110] Mixing 40 parts of a second acrylate monomer, 0.01 parts of a catalyst, and 0.01 parts of a polymerization inhibitor to obtain a premix E;

[0111] S2, premix A and 200 parts of polytetrahydrofuran diol with a molecular weight of 4000Mn were added into a reactor in sequence, stirred at a speed of 120rpm, heated to 65°C, and vacuum-0.07±0.01Mpa was opened to obtain intermediate A;

[0112] S3, lower the temperature in the kettle to 55°C, add 52.4 parts of liquid isocyanate, and open the vacuum -0.07±0.01MPa, stir at a speed of 100rpm for 30 minutes, add premix B into the reactor and open the vacuum -0.07±0.01Mpa, stir at a speed of 60rpm, control the temperature not exceeding 75°C, stir for 60 minutes, and obtain intermediate B;

[0113] S4, adding premix C and 200 parts of polycarbonate diol with a molecular weight of 2000Mn into the kettle and opening the vacuum -0.07±0.01Mpa, stirring at a speed of 60rpm, controlling the temperature not to exceed 75°C, stirring for 90 minutes to obtain intermediate C;

[0114] S5, adding premix D to intermediate C, and turning on the vacuum of -0.07±0.01Mpa, stirring at a speed of 60rpm, controlling 70°C, and stirring for 120 minutes to obtain intermediate D;

[0115] S6. Add premix E and 47.4 parts of blocked isocyanate acrylate monomer into the kettle and open the vacuum of -0.07±0.01 MPa, raise the temperature to 90°C, stir at a speed of 60 rpm for 60 minutes and then discharge the material to obtain acrylate prepolymer 1.

[0116] After calculation, the acrylic ester prepolymer 1 includes, by weight:

[0117]

[0118] Preparation Example 2-5

[0119] Preparation Example 2-5 adopts a method similar to Preparation Example 1, changing the material composition to prepare acrylate prepolymers 2-5 respectively.

[0120] Commercially available examples

[0121] The commercially available acrylate prepolymer BR3741AJ was selected.

[0122] The main material ratios of acrylate prepolymers are shown in Table 1:

[0123] Table 1

[0124]

[0125]

[0126] Example 1

[0127] A high-performance environmentally friendly UV adhesive for batteries, comprising the following raw materials in parts by weight:

[0128] (1) 40 parts of the acrylic acid ester prepolymer of Preparation Example 1;

[0129] (2) The first acrylate monomer, 60 parts in total, comprises:

[0130]

[0131] (3) Photoinitiator, 6 parts in total, including:

[0132] Photoinitiator 1173 3 parts,

[0133] Photoinitiator 819 3 parts;

[0134] (4) thixotropic agent: R972, 10 parts;

[0135] (5) Other additives, 2.4 parts in total, including:

[0136]

[0137]

[0138] The preparation method of high-performance environmentally friendly UV adhesive for batteries includes the following steps:

[0139] Step 1: using the acrylate prepolymer of Preparation Example 1;

[0140] Step 2: Add the acrylate prepolymer, 50% of the first acrylate monomer, a photoinitiator, a defoamer, an antioxidant and a matting agent into a double planetary stirring kettle, heat to 45°C, start stirring at 20rpm, disperse at 200rpm, and stir for 60 minutes;

[0141] Step 3: After 300-mesh double-layer gravity filtration, add thixotropic agent in batches according to proportion; stir at high speed 45 rpm, disperse at 1000 rpm, stir for 60 minutes, control the temperature below 40°C, and obtain a semi-finished product;

[0142] Step 4: Grind the semi-finished product with three rollers at a speed of 200 rpm and a speed of 40 μm in and 20 μm out. Add the ground material, the remaining first acrylate monomer and other additives into the reactor, stir at 45 rpm and disperse at 1000 rpm for 60 minutes, control the temperature below 40°C, turn on the vacuum at -0.07±0.01 MPa, and perform vacuum degassing and discharge at a stirring speed of 15 rpm and a dispersion speed of 100 rpm.

[0143] Embodiment 2-8

[0144] The preparation process of Examples 2-8 is the same as that of Example 1, but the materials and amounts used are different.

[0145] Comparative Example 1

[0146] Comparative Example 1 uses commercially available acrylate prepolymer, and the remaining parameters and preparation method are the same as those of Example 1.

[0147] Comparative Example 2

[0148] Comparative Example 2 uses commercially available acrylate prepolymer, and the remaining parameters and preparation method are the same as those of Example 4.

[0149] The main material ratios of Examples 1-8 and Comparative Examples 1-2 are shown in Table 2:

[0150] Table 2

[0151]

[0152]

[0153] Test Method

[0154] (1) Surface dryness test

[0155] Apply the glue on the flat surface of the release film, control the thickness to 250±20um, and cure it in an LED 365nm curing box at 1.2W / cm 2After irradiation with a power of 1000 nm for 3 seconds, take it out and let it stand for 5 minutes. Use the finger touch method to confirm whether the surface is sticky. If it is sticky, it means the surface is not dry, which is counted as NG. If it is not sticky, it means the surface is dry, which is counted as PASS.

[0156] (2) Viscosity test

[0157] After the rotor viscometer is calibrated to zero, use 0.4mL of glue, 51# rotor at 50rpm for 2 minutes and read the data;

[0158] (3) Thixotropy test

[0159] Same as above, test the viscosity at 50rpm and 5rpm, thixotropy = 5rpm viscosity data / 50rpm viscosity data;

[0160] (4) Curing depth test

[0161] Squeeze 3.5g of glue onto the PUR hose end cap and scrape it flat. Put it into the LED365nm curing box at 420mW / cm 2 After irradiating with power of 10s, take out the upper cured material, wipe off the uncured glue on the back and test the thickness with a micrometer to read the minimum value;

[0162] (5) Elongation at break test

[0163] Squeeze a proper amount of glue on the mold and cover it with 20g of release film. Scrape the glue on the back of the release film and put it into the LED365nm curing box at 420mW / cm 2 After irradiation with a power of 10s, the sample was taken out and tested using a tensile machine at a speed of 100mm / min. Elongation at break = breaking length / 10×100%;

[0164] (6) Shear strength test

[0165] Stick three 2mm wide black tapes adjacent to the silver aluminum-plastic film (hot pressing), remove the middle one, cut the aluminum-plastic film into 10mm wide strips along the vertical direction of the tape, tear off the release film of the tape, apply glue and stick it with the PC sheet in the LED light box at the 3rd layer position to cure for 24s, and test at a speed of 5mm / min;

[0166] (7) Insulation test

[0167] A 0.25mm thick adhesive film is placed on the aluminum foil, and then another layer of aluminum foil is placed on top (the contact parts of the two layers of aluminum foil are isolated with tape). A square silicone pad with a side length of 15mm is placed on top of the upper aluminum foil, and then pressed with a 500g weight. The upper and lower aluminum foils are respectively connected to the output and loop fixture of the equipment. The resistance of the glue is tested at 100V. The volume resistivity = resistance × 0.9. When the volume resistivity value is higher than 10 9 Ω·m, it is considered as PASS;

[0168] (8) Glass transition temperature Tg test

[0169] The glue is made into a 0.2-0.3mm thick, 6-8mm wide, and 12-16mm long film, and the film is stretched using a DMA850 dynamic thermal mechanical analyzer fixture. The temperature is raised from -40°C to 120°C at a heating rate of 3°C / min, an amplitude of 10um, a frequency of 10hz, and a pre-stretch of 125%. The extreme point temperature of the loss tangent tanδ is Tg.

[0170] The above test was carried out for Examples 1-8 and Comparative Examples 1-2, and the test results are shown in Table 3:

[0171] Table 3

[0172]

[0173]

[0174] The UV adhesive prepared by using the self-made acrylate prepolymer in Example 1-8 has a viscosity of less than 5000cps, a thixotropy of greater than 3.5, preferably greater than 3.8, more preferably greater than 4, a curing depth of greater than 0.5mm, preferably greater than 0.6mm, and a curing temperature of 1.2W / cm 2 UV ultraviolet irradiation can dry the surface for 3-5 seconds, with low viscosity, high thixotropy, short curing time, high curing depth and other characteristics, simple gluing process; and Tg ≥ 70 ℃, elongation at break ≥ 550%, shear strength ≥ 5MPa, UV glue has the advantages of high bonding strength, good colloid flexibility and reliability; resistivity ≥ 10 9 Ω·m, excellent insulation performance. However, the UV glue prepared by commercially available acrylate prepolymer has high viscosity, low thixotropy, inconvenient glue application, relatively long curing time, relatively low bonding strength and Tg, and relatively weak reliability.

[0175] In summary, the high-performance environmentally friendly UV glue for batteries provided by the present invention has the characteristics of low viscosity, high thixotropy, convenient application and short curing time, good flexibility of the cured colloid, high bonding strength and excellent heat resistance and insulation performance, etc., which ensures that the edge sealing layer of the battery is always stable during long-term use, avoids battery failure problems caused by failure of edge sealing glue in traditional technologies, and enhances the safety and reliability of soft-pack batteries in complex environments.

[0176] The above introduces the preferred embodiments of the present invention, which is intended to make the spirit of the present invention clearer and easier to understand, but is not intended to limit the present invention. Any modifications, substitutions, and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-performance environmentally friendly UV adhesive for batteries, characterized in that: In parts by weight, it comprises the following raw materials: The raw materials of the acrylic ester prepolymer include compounded polyol, isocyanate and a second acrylic ester monomer; the compounded polyol includes a flexible polyol and a hard polyol compounded in a molar ratio of 1:(1-5).

2. The high performance environmentally friendly UV adhesive according to claim 1, characterized in that: The flexible polyol has a molecular weight of 1000-5000 Mn and includes at least one of polyether polyol and polyolefin polyol; The hard polyol has a molecular weight of 500-2500 Mn and comprises polyester polyol.

3. The high performance environmentally friendly UV adhesive according to claim 2, characterized in that: The first acrylate monomer includes at least one of a monofunctional acrylate monomer and a high-functional acrylate monomer, and does not contain a methacrylate monomer.

4. The high-performance environmentally friendly UV adhesive according to any one of claims 1 to 3, characterized in that: The acrylic acid ester prepolymer comprises the following raw materials in parts by weight: The isocyanate includes diisocyanate, and the molar ratio of isocyanate to the flexible polyol is (1-4): 1; The molar ratio of isocyanate-terminated acrylate monomer to rigid polyol is (1-5):(1-3); The second acrylate monomer is an acrylate monomer that is non-reactive with respect to the isocyanate.

5. The high performance environmentally friendly UV adhesive according to claim 4, characterized in that: The isocyanate-terminated acrylate monomer includes at least one of isocyanate ethyl acrylate and isocyanate ethyl methacrylate; and / or The isocyanate-terminated acrylate monomer is prepared by prepolymerization of isocyanate and hydroxyl-containing acrylate monomer, wherein the mass ratio of isocyanate to hydroxyl-containing acrylate monomer is (15-60): (8-35).

6. The high-performance environmentally friendly UV adhesive according to any one of claims 1 to 5, characterized in that: At least one of the following is met: 1) The flexible polyol includes one or more of polyethylene glycol polyol, polypropylene glycol polyol, polytetramethylene glycol polyol, tetramethylene glycol-propylene oxide copolymer glycol, polyethylene polyol, polypropylene polyol, polybutadiene polyol, and polyisoprene polyol; 2) The hard polyol includes one or more of aliphatic polyester polyol, aromatic polyester polyol, polycaprolactone polyol, and polycarbonate polyol; 3) The isocyanate includes one or more of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.

7. The high performance environmentally friendly UV adhesive according to any one of claims 1 to 5, characterized in that: At least one of the following is met: 1) The photoinitiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzophenone, 2,4-dihydroxybenzophenone, Michler's ketone, (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, bicyclic monoterpenoid compounds, and 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone; 2) The thixotropic agent includes at least one of nano fumed silica, nano calcium carbonate, nano zinc oxide, nano zirconium oxide, nano aluminum oxide, precipitated silica, nano talc, organic bentonite, and polyamide wax; 3) The other auxiliary agents include one or more of coupling agents, matting agents, defoaming agents, antioxidants, and colorants.

8. The method for preparing the high-performance environmentally friendly UV adhesive for batteries according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, preparing an acrylate prepolymer; Step 2, stirring and mixing the acrylate prepolymer, part of the first acrylate monomer, the photoinitiator, and part of other additives at 40-50° C. to obtain a mixture; Step 3, filtering the mixture, adding a thixotropic agent, and stirring at a temperature below 40° C. to obtain a semi-finished product; Step 4: Grind the semi-finished product and mix it with the remaining first acrylate monomer and other additives, stir it at a temperature below 40° C., and perform vacuum degassing to obtain the UV adhesive.

9. The preparation method according to claim 8, characterized in that: The step one includes the following steps: S1. Preparation of premixes A to E: Mixing a portion of the second acrylate monomer and 30-60% of a polymerization inhibitor to obtain a premix A; Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix B; Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix C; Mixing a portion of the second acrylate monomer and 20-30% of a catalyst to obtain a premix D; Mixing a portion of the second acrylate monomer, 20-30% of the catalyst and 40-70% of the inhibitor to obtain a premix E; S2, mixing the premix A and the flexible polyol under vacuum at 60-70° C. to obtain an intermediate A; S3, cooling to 50-60°C, adding isocyanate to intermediate A, stirring under vacuum, then adding premix B, mixing under vacuum at below 75°C, to obtain intermediate B; S4, adding premix C and hard polyol to intermediate B, mixing under vacuum at below 75° C. to obtain intermediate C; S5, adding premix D to intermediate C, mixing under vacuum at 65-75° C. to obtain intermediate D; S6. Add the premix E and the isocyanate-terminated acrylate monomer to the intermediate D, stir and heat to 85-95° C. under vacuum to obtain the acrylate prepolymer.

10. The preparation method according to claim 9, characterized in that: The weight ratio of the second acrylic acid ester monomer in the premix A, premix B, premix C, premix D and premix E is 1:(1-3):(1-3):(1-4):(1-6).

Citation Information

Patent Citations

  • Edge sealing method of cylindrical soft package battery and cylindrical soft package battery

    CN113113703A

Cited By

  • UV light-cured shielding glue as well as preparation method and application thereof

    CN121379486A

  • Uv light-cured masking glue, preparation method and application thereof

    CN121379486B